Factors associated with early childhood development: results from the Brazilian National Survey on Child Nutrition (ENANI-2019) - Gilberto Kac; Nadya Helena Alves-Santos; Dayana Rodrigues Farias; Nathalia Cristina Freitas-Costa; Raquel Scincaglia; Paula Normando; Inês Rugani; Elisa Maria de Aquino Lacerda; Sandra Crispim; Alexandra Valeria Maria Brentani; Claudia Regina Lindgren Alves (BMJ Public Health)
Introduction The full achievement of early childhood development (ECD) is a human right and adhering to the nurturing care framework may facilitate it.Objective To evaluate the association between distal and proximal variables and developmental quotient (DQ).Methods Data from 14 159 children <5 years were evaluated in the Brazilian National Survey on Child Nutrition. The Survey of Well-being of Young Children—Brazilian version milestones questionnaire was used to evaluate ECD. The developmental age was estimated using the graded response models. DQ was calculated by dividing developmental age by chronological age. The expected age milestones are attained when DQ=1. DQ predictors were defined considering distal and proximal levels/variables using a multiple linear regression model and a hierarchical approach.Results The DQ mean was significantly lower among children aged 36–59 months (0.91 (0.88 to 0.93)), boys (1.03 (1.01 to 1.06)) and those from the North region (0.98 (0.93 to 1.04)) compared with children aged 1–35 months (1.18 (1.15 to 1.22)), girls (1.11 (1.08 to 1.13)) and from the Southeast region (1.11 (1.07 to 1.16)). For children aged 1–35 months, DQ was inversely associated with emergency C-section (β=−0.08; p<0.01), consumption of ultra-processed food (β=−0.33; p<0.01), and positively associated with attendance at daycare/school (private: β=0.09; p=0.02 and No: β=0.12; p<0.01). For children aged 36–59 months, attendance to private daycare/school (β=0.08; p<0.01) was positively associated with DQ, and small for gestational age at birth (β=−0.05; p=0.01) and access to public health services (no-primary care) (β=−0.07; p<0.01) were inversely associated with DQ.Conclusions Adverse health, nutrition and learning factors predicted the ECD, demonstrating an inequitable environment for Brazilian children. These findings indicate a need for public policies to ensure social and health equity in early childhood.